The Mauritian Experience - Tahalooa, S (Journal of Malaysian and Comparative Law, 2019)
The Government of Mauritius initiated the first major reform in Public Procurement (that was successful) in 2006. The Public Procurement Act based on 1994 UNCITRAL Model Law was promulgated in January 2008. The implementation phase did not encounter any major hurdle. This may be due to the successful change management programme which was put in place. Furthermore, an extensive capacity building programme started since 2007 and continued in subsequent years. The contributions of the three institutions namely Procurement Policy Office, Central Procurement Board and Independent Review Panel, were instrumental to the smooth implementation of the new procurement legislation. In 2010, the government decided to undergo a second major reform in public procurement. The Institutional Structure (both at national and public body’s level) and Legal Framework are undergoing a complete review. The focus is also on professionalizing the procurement function. Specifically the reform focuses on: simplifying the procurement system, combatting corrupt practices, delivering cash and non-cash benefits and applying sustainable principles. e-Procurement, Sustainable Public Procurement, Framework Agreement and Life Cycle Costing are the key instruments that aim to achieve these objectives.